1953
DOI: 10.1139/v53-005
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylation and Epoxidation of Rapeseed Oil Derivatives With Subsequent Pyrolysis and Ammonolysis

Abstract: A method was developed to follow the hydroxylation of rapeseed oil and erucic acid derivatives with peracetic acid. Peracetic acid prepared insitu was found to be equally as effective as the preformed acid in hydroxylation of methyl erucate. Among the compounds synthesized were ethyl 13,14-dihydroxybehenate, methyl 13,14-oxidoerucate, ethyl 13,14-diacetoxybehenate, and methyl 13,14(14,13)-hydroxyacetoxybehenate which were subsequently pyrolyzed at approximately 300 °C with p-toluenesulphonic acid as catalyst. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The epoxidised oil in addition to the above showed a distinct doublet absorption at 823 cm -1 characteristic of the C-O-C oxirane stretch usually observed in the naturally epoxidised vegetable oils [15]. The absence of hydroxyl band in the IR spectra of the epoxidised PKCP oil indicates the superiority of the dioxirane epoxidation of triglyceride over the peracid epoxidation which has been noted to cause oxirane ring opening to the diols [6,16].…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The epoxidised oil in addition to the above showed a distinct doublet absorption at 823 cm -1 characteristic of the C-O-C oxirane stretch usually observed in the naturally epoxidised vegetable oils [15]. The absence of hydroxyl band in the IR spectra of the epoxidised PKCP oil indicates the superiority of the dioxirane epoxidation of triglyceride over the peracid epoxidation which has been noted to cause oxirane ring opening to the diols [6,16].…”
Section: Resultsmentioning
confidence: 78%
“…Furthermore the epoxides prepared by these methods must be instantly separated from the acids to avoid the oxirane ring opening which leads to lower oxirane value. It has also been generally observed that peracid oxidation of unsaturated vegetable oils do not appear to go to completion [4][5][6]. To circumvent these problems Sonnet and Foglia [7] suggested the use of dioxiranes.…”
Section: Introductionmentioning
confidence: 99%